Transformasi Budaya Religius: Strategi Implementasi Pendidikan Agama Islam di Sekolah Menengah Pertama Islam DDI Sangatta Utara - Putri Paradiva Arifin; Ramdanil Mubarok; Muhammad Imam Syafi'i (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2024)
This research examines the implementation of Islamic Religious Education at Islamic Middle School DDI Sangatta Utara with a focus on the transformation of religious culture. Amid the challenges of globalization and modernization, schools need to develop adaptive strategies for teaching religious values ​​that are relevant to students' daily lives. Qualitative descriptive research methods were used to explore this transformation process at DDI Sangatta Utara Islamic Middle School. The research results show that the integration of Islamic values ​​in an integrated curriculum and the use of interactive learning methods such as group discussions and collaborative projects can increase students' understanding and relevance of lesson material. However, this process is faced with several challenges, including limited resources, resistance to change on the part of teachers, and the need for better training for teaching staff. This study provides a theoretical contribution to enriching understanding of the transformation of religious culture in Islamic education, while practically offering guidance for the development of more effective and contextual Islamic Religious Education strategies.